Accelerated intermittent theta burst stimulation for pharmacological treatment‐resistant bipolar depression: Protocol for double‐blind, randomized, sham‐controlled trial - Taro Kishi; Kenji Sakuma; Shun Hamanaka; Yasufumi Nishii; Kosei Esaki; Yueren Zhao; Yuki Matsuda; Shinsuke Kito; Nakao Iwata (PCN Reports)
Abstract Background With 30%–50% of people with bipolar depression (BDep) not responding to multiple pharmacological treatments, alternative therapies are needed. Accelerated intermittent theta burst stimulation (aiTBS) over the left dorsolateral prefrontal cortex (L‐DLPFC) has been employed for individuals with pharmacological treatment‐resistant major depressive disorder (TR‐MDD). Imaging studies have revealed reduced regional activity of the L‐DLPFC for both TR‐MDD and pharmacological treatment‐resistant BDep (TR‐BDep), suggesting that aiTBS over the L‐DLPFC may be beneficial for people with TR‐BDep. Methods A 6‐week, double‐blind, sham‐controlled, randomized trial will be conducted to compare the efficacy and safety of aiTBS to the L‐DLPFC in people with TR‐BDep (jRCTs042240019). Fifty iTBS sessions (1800 pulses/session) will be delivered in 10 daily sessions over 5 consecutive days at 90% resting motor threshold. This aiTBS protocol is termed as Fujita Neuromodulation Therapy for Bipolar Depression (FNT‐BD). Twenty‐two participants (both sexes, aged 18–64 years) with TR‐BDep (DSM‐5‐TR, Type I) will be recruited. The response rate at any given week of follow‐up will be the primary efficacy outcome, defined as a reduction of ≥50% in the Montgomery Åsberg Depression Rating Scale (MADRS) score. Other outcomes will include MADRS score changes, remission rate (10 ≥ MADRS score), Clinical Global Impression‐Improvement score, Clinical Global Impression‐Severity score, discontinuation rate, and incidence of individual adverse events. Results We anticipate that individuals who receive the aiTBS treatment show significant improvement in depressing symptoms compared to those receiving sham treatment. Conclusions This study will provide valuable evidence for both patients with TR‐BDep and clinicians.